The Second Plan Madras State Review of Progress for 1956-57 and 1957-58 and Programme for 1958-59 - Planning Commission (Planning Commission, 1958)
The Second Five-Year Plan provides a broad frame-work within which annual plans have to be worked out in detail every year. On Account of the reorganization of States which came into effect on 1st November 1956 and certain other factors, the State Government could not publish their Plan for 1956-57. The programme for 1957-58 was published in May 1957.
Madras State